Stereotactic Body Radiotherapy for Small Unresectable Hepatocellular Carcinomas. Issue 6 (June 2019) - Yeung, R.; Beaton, L.; Rackley, T.; Weber, B.; Hamm, J.; Lee, R.; Camborde, M.; Pearson, M.; Duzenli, C.; Loewen, S.K.; Liu, M.; Ma, R.; et al.
Abstract: Aims: Stereotactic body radiotherapy (SBRT) is an option for the treatment of hepatocellular carcinoma (HCC) in patients ineligible for standard local therapies. This study reports on the safety and efficacy of SBRT in small HCC tumours (≤5 cm) in the province of British Columbia. Materials and methods: Between March 2011 and July 2015, 31 patients with Child–Pugh Class A or B, with small HCCs measuring ≤5 cm were treated with SBRT at our institution. Primary end points were local control, progression-free survival, overall survival and toxicity. Results: Thirty-four hepatomas (median size 3.3 cm, range 1.3–5.0 cm) were treated. The median follow-up was 18.3 months. Twenty-six patients (84%) had received previous liver-directed treatments. Most patients (88%) were treated with 45 Gy in three or five fractions. Six patients (19%) had worsened Child–Pugh score by two or more points during follow-up; overall 32% of patients experienced ≥ grade 3 + toxicities. One-year local control and overall survival were 94 and 84%, respectively. One-year progression-free survival was 49%; 81% of patients with disease progression received further HCC therapy. On univariate analysis, small tumour size predicted for improved overall survival ( P  = 0.01) whereas prescription biological equivalent dose (BED10 ) ≥100Gy10 approached significance ( P  = 0.06). Conclusion: SBRT provides high local control to small inoperable HCC. SBRT can be delivered safely even after previous liver-directed therapies and further liver therapies can follow treatment with SBRT. Although overall 32% of patients experienced ≥ grade 3 + toxicities, and 19% had a deterioration in Child–Pugh score of two or more points, these changes were mainly transient with minimal clinical impact. Despite excellent local control, disease progression outside of the irradiated site remains prominent. Further studies are warranted to examine combined therapy approaches to maximise disease control. Highlights: SBRT is an effective treatment for small inoperable HCCs. SBRT provides excellent local control with control rates of 94% at 1 and 2 years. SBRT can be delivered safely even after previous liver-directed therapies. SBRT can be used as a bridge to liver transplantation for small HCCs.